Patient carrier of human t-lymphotropic virus type 1 (HTLV type 1): An experience report - Francilany Fabiola Vilhena Vieira; Jamile da Silva Corrêa; Rejane de Almeida Martins; Debora dos Santos Cardoso; Taís Amaral Dantas; Elen de Oliveira Vieira Bandeira; Izabela Cristina da Silva dos Santos; Elaine Fabricia Oliveira da Silva; Arimatéia Portela de Azevedo (Revista Feridas, 2022)
Objective: To carry out an experience report on nursing assistance to a patient with human T- lymphotropic virus type 1 (HTLV type 1). Methodology: Descriptive, exploratory, retrospective and quantitative study. Results: New arrival not soon attended to reference hospital, native of his residence, already in convalescence for several years with HTLV TYPE 1, or patient A.P.O, 58 years old. Patient with chronic use of corticosteroid and nine days after death, after cardiorespiratory arrest due to kidney failure (among other complications) and was found to be dead after 45 minutes of resuscitation. A constant observation of the (balanced) feeding offered, observation of hypo or hyperglycemia sinuses, decubitus change, padding of bone prominence, stimulation of active and passive movements for some two nursing care offered to this patient. Conclusion: During the absence of a public program aimed at the care of the HTLV carrier, there are necessary actions that provide assistance, not to monitor and control the viral infection, such as the active search for infected people, the orientation of two families and their relatives, to carry out the clinical and laboratory examinations for the prevention and / or early detection of illnesses and investigation of epidemiological characteristics related to infection. Descriptors: sickness, preventive care, sociodemographic